Sex- and gender-related differences in inflammatory bowel diseases - Blumenstein, Irina; Sonnenberg, Elena (Frontiers in Gastroenterology, 2023)
This review provides an overview of the current data regarding sex- and gender-specific aspects in patients with inflammatory bowel diseases. A particular focus will be on disease course, medical and surgical treatment strategies, psychosocial differences, and special requirements during pregnancy and family planning. The most significant and clinically meaningful gender differences in IBD relate to psychosocial functioning. Although depression, fatigue, anxiety disorders, eating disorders, and sexual dysfunction also occur in male IBD patients, women seem to be affected much more frequently and severely in these areas.